PENGARUH FINANCIAL KNOWLEDGE DAN FINANCIAL ATTITUDE TERHADAP FINANCIAL MANAGEMENT BEHAVIOR PADA MAHASISWA ADMINISTRASI BISNIS - Indah Andri Yani; Nanda Ameliany (Program Studi Administrasi Bisnis, 2022)
This study aims to determine and analysis The Effect Of Financial Knowledge and Financial Attitude On Financial Management Behavior In Business Administration Students, Faculty Of Social and Political Sciences, Malikussaleh University. The population in this study were Business Administration Students, Faculty Of Social and Political Sciences, Malikussaleh University, class of 2018 - 2021. The number of samples in this study was 75 students with a proportionate stratified random sampling technique. Data collection methods are questionnaires and interviews. Analysis technique using multiple linier regression analysis. The results of this study indicate that simultaneously Financial Knowledge and Financial Attitude have a significant and significant effect on Financial Management Behavior. Partially (T test) Financial Knowledge and Financial Attitude variables have a positive and significant effect on Financial Management Behavior. The results of multiple linear regression analysis show that Financial Knowledge and Financial Attitude have a positive effect on Financial Management Behavior and the results of the coefficient of determination obtained R Square number of 0,558 indicates that Financial Knowledge (X1) and Financial Attitude (X2) is 55,8% while the remaining 44,2% can be explained by factors not examined.